Assessment of Tooth Extraction Anxiety and Depression in Older Adults - Maya Madhuri, Oam Parkash, Samreen Malik, Tahseen Shabbir, Arifa Haque, Tahera Ayub, Salman Shams (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Dental anxiety is a common phenomenon among patients of all ages, but the issue becomes particularly relevant for older adults who may have more complex dental needs or medical conditions that could impact their dental health. Objectives: The main objective of the study is to assess the tooth extraction anxiety and depression in older adults. Material and methods: The research article aimed to investigate the prevalence of tooth extraction anxiety and depression among older adults receiving dental care at the Oral and Maxillofacial Surgery Department of Liaquat University of Medical and Health Sciences in Jamshoro. The study was conducted over a period of 12 months, from January 2019 to December 2019, and included a sample of 150 patients aged 65 years and above. Results: The majority of the participants were male (60%), and the mean age of the sample was 71.6 years (SD= 5.8 years). The educational level of the participants was relatively low, with 71% of the sample having less than a high school education. The most common medical comorbidities reported by the participants were hypertension (62%), diabetes (32%), and heart disease (14%). Conclusion: In conclusion, tooth extraction anxiety and depression are common in older adults, with nearly half of the participants in this study reporting symptoms following the procedure. Female participants in the 60+ age group were found to be more likely to report anxiety and depression, as were those with pre-existing medical conditions. Keywords: Dental, Anxiety, Depression, Adults, Patients